HOW ARE INNOVATIVE PROJECTS BORN IN THE PROFESSIONAL MASTERS IN EDUCATION? REFLECTIONS ON TEACHING, SCHOOL AND CURRICULUM - Souza, Mariana Aranha de; Bussolotti, Juliana Marcondes; Prospero da Cunha, Virginia Mara; Arantes Fazenda, Ivani Catarina [UNESP] (Fundacao Univ Tocantins, 2020)
This article intends to reflect how Innovative Projects are born in the Professional Master's in Education, how they take place and what are their possibilities of reverberation in the daily life of schools. For this, the process of elaboration and implementation of Projects considered Innovative by 11 groups, formed by 31 master students who studied the subject School, Curriculum and Diversity in 2019, was analyzed. The results indicate that the master students consider this methodological strategy as important for their professional development and teaching process as researchers. The projects demonstrate the diversity of themes, prioritizing the participation of the participating students and teachers, including in the same project, different teaching modalities and different schools. Master's students affirm the projects allowed to articulate the theoretical and practical dimensions, in addition to contributing to their own professional development, coined in collective experiences. They demonstrated that they understand that innovative projects are constituted from an interdisciplinary understanding of knowledge and that they materialize in the movement of dialogue, exchange, exposure and risk, in different times and formative spaces.
Keywords: Interdisciplinarity; Teacher training; Innovative Projects; Professional Master in Education